The School and the Forms new of Convivence - Estrada, Miguel Ángel (2016)
In actuality, in schools it is increasing the negative forms of cohabitation, they are being considered as new even though they have always been present, that is because they have little time that are being investigated. The main one is harassment scholar and it presented in four categories: harassment psychological in the work (mobbing), harassment of student toward student (bullying), harassment of student to for teacher and harassment of teacher toward student.